The effects of sanctions on Russian banks in TARGET2 transactions data - Constantin Drott; Stefan Goldbach; Volker Nitsch (Deutsche Bundesbank, 2022)
This short paper examines the effect of financial sanctions at the most disaggregated level possible, individual bank accounts. Using data from the Eurosystem's real-time gross settlement system TARGET2, we provide empirical evidence that sanctions imposed by the European Union on Russian banks following the country's military interventions in Ukraine in 2014 and 2022 have sizably reduced financial transactions with sanctioned Russian bank accounts. Among the various sanction measures taken, exclusion from SWIFT, a global provider of secure financial messaging services, turns out to have the largest effects.
Keywords: F38; F51; G28; 330; financial flows; transactions; restrictions